In Vivo Neuroprotective Activity of Erythropoietin-Alginate Microspheres at Different Polymer Concentrations - Hariyadi, Dewi Melani (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of this study was to evaluate in vivo neuroprotectant activity of erythropoietin-alginate microspheres with different concentrations to modify release to reduce the administration frequency of erythropoietin. Materials and Methods: Sodium alginate and CaCl2 were used to produce microspheres using aerosolization technique and erythropoietin as model. Balb/c-strain mice (Mus musculus) were used to study in vivo activity in terms of locomotor activity and glutathione peroxidase (GSHPx) activity as well as percentage of reticulocytes. Results and Discussion: Erythropoietin-alginate microspheres demonstrated neuroprotectant activity such as locomotor activity and GSHPx activity compared to erythropoietin alone and blank microspheres. Increased polymer concentrations (1–3%), however, did not have a significant effect on changes of the effectiveness of the activity of microspheres. Interestingly, these results also showed that erythropoietin-alginate microspheres which contain only 5000 units produced a high percentage of reticulocytes. Conclusion: The study indicates that erythropoietin-alginate microspheres showed the potential activity of erythropoietin-alginate microspheres although in low concentration. Increased concentrations of polymers showed similar effects in locomotors activity and GSHPx enzyme activity as parameters of neuroprotectant activity.